Reliability and validity of a pool-based maximal oxygen uptake test to examine high-intensity short-duration freestyle swimming performance - Nagle, E. F.; Nagai, T.; Beethe, A. Z.; Lovalekar, M. T.; Zera, J. N.; Connaboy, C.; Abt, J. P.; Beals, K.; Nindl, B. C.; Robertson, R. J.; Lephart, S. M. (The Journal of Strength and Conditioning Research, 2019)
A modality-specific swimming protocol to assess maximal oxygen uptake (VO2maxsw) is essential to accurately prescribe and monitor swimming conditioning programs. Consequently, there is a need for a reliable and valid graded intensity swimming pool test to accurately assess VO2maxsw using indirect calorimetry. The purpose of this study was to assess (a) reliability of an intensity self-regulated swimming pool test of VO2maxsw and (b) validity of a VO2maxsw test using performance swim (PS) time as the criterion. Twenty-nine men (n = 15) and women (n = 14) (age, 23 ± 6.4 years; body mass index, 23.5 ± 3.0 kg·m-2) performed 2 swimming pool VO2maxsw trials (VO2maxsw A and VO2maxsw B), and 2 PS tests (45.7 m [31.20 ± 4.5 seconds] and 182 m [159.2 ± 25.5 seconds]). For test-retest reliability (trials A vs. B), strong correlations (p < 0.05) were found for VO2maxsw (ml/kg/min) (r = 0.899), O2 pulse (ml O2/beat) (r = 0.833), and maximum expired ventilatory volume (L·min-1) (r = 0.785). For performance validity, moderately strong correlations (p < 0.05) were found between VO2maxsw A and 45.7-m (r = -0.543) and 182-m (r = -0.486) swim times. The self-regulated graded intensity swimming pool protocol examined presently is a reliable and valid test of VO2maxsw. Studies should consider the suitability of a VO2maxsw test for military personnel, clinical populations, and injured athletes.